PANDANGAN NEO SUFISME NURCHOLIS MADJID (Studi Tentang Dialektika Antara Tasawuf Klasik dan Tasawuf Modern di Indonesia) - Abidin, Munirul (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2008)
This research is to describe: (1) the background of emergence of Nurcholish Madjid' s thinking about Neo-Sufism. (2) the substance of Neo-Sufism according to Nurcholish Madjid and it's implication to the life of Islamic community. (3) to describe it's existence between classical Sufism and modern Sufism. This research is library research. The data in this research are qualitative data from the books and documents that relate to the topic. The collected data are analyzed by content analysis technique. This research find that two factor cause the emergence of Nurcholish Madjid's thinking about Neo-Sufism: (1) historical and scientific factor that sunni Sufism, philosophical Sufism and modern Sufism are contradicting and blaming each others on their concept. (2) actual factors that is, the emergence of spiritual crisis in the western country and their consciousness to repair it by studying Sufism teaching. Neo-Sufism is the continues of the classical Sufism and modern Sufism thinking, but it try to combine between them. If the classical Sufism stress on spiritual experience, spiritualism, uzlah, wirid, zikir and kasyaf, and take away the profane affairs, and modern Sufism see that uzlah, kasyaf and spiritual experience on classical Sufism as bid'ah and khurafat, Neo Sufism try to combine them by saying that spiritual experience, uzlah, and kasyaf are importance but not to far away from profane life. According to Neo Sufism, to be sufi is not throw away profane life but we still can be sufi although to be active in profane life. Nurcholish Madjid' s thinking o n Neo-Sufism is the consistence of Ibnu Taimiyah-Ib nu Qayyim Al-Juaziyah-Fazlurrahman an d Hamka thinking.